2011
DOI: 10.1016/j.neuron.2010.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Tactile Motion Integration in Somatosensory Cortex

Abstract: Summary How are local motion signals integrated to form a global motion percept? We investigate the neural mechanisms of tactile motion integration by presenting tactile gratings and plaids to the fingertips of monkeys, using the tactile analogue of a visual monitor, while recording the responses evoked in somatosensory cortical neurons. In parallel psychophysical experiments, we measure the perceived direction of the gratings and plaids. We identify a population of somatosensory neurons that exhibit integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 46 publications
4
75
1
Order By: Relevance
“…Are there equivalent cells in touch? In [36] the authors identified a population of somatosensory neurons accounting for the perceived direction of the stimulus on the skin and they might be analogous to the head direction cells in the hippocampus. However, to the best of our knowledge an analogy to place or grid cells that would perform path integration has not been found in the tactile system so far.…”
Section: Discussionmentioning
confidence: 99%
“…Are there equivalent cells in touch? In [36] the authors identified a population of somatosensory neurons accounting for the perceived direction of the stimulus on the skin and they might be analogous to the head direction cells in the hippocampus. However, to the best of our knowledge an analogy to place or grid cells that would perform path integration has not been found in the tactile system so far.…”
Section: Discussionmentioning
confidence: 99%
“…This idea was based on a previous report by Deibert et al 1999 (see also Amedi et al 2002), who employed functional magnetic resonance to demonstrate that visual cortical areas are also active during tactile object recognition. In fact, there is evidence of mechanisms of tactile integration that are analogous to those related to visual processing (Bensmaia et al 2006;Pei et al 2011), thus suggesting an integration between both modalities. We also assume that in the central nervous system there are multisensory neurons participating in the tactile-visual cross-modal integration of signal and noise inputs (Barth and Brett-Green 2004;Calvert and Lewis 2004;Collins et al 2005;Gentile et al 2011;Kadunce et al 1997;Stein et al 1988Stein et al , 1996Wallace et al 1992).…”
mentioning
confidence: 99%
“…The somatosensory system is typically considered to be a spatial sense, one that draws strong analogies with the visual system (28)(29)(30). The extraction of information from oscillations of the somatosensory epithelium implies a complementary mode of processing for the primate somatosensory system, one that draws analogies with the auditory system (31) and with the vibrissal system of rodents (32).…”
Section: Discussionmentioning
confidence: 99%